2018
DOI: 10.3390/ijerph15020341
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Interventions for Parent Carers of Children with Autistic Spectrum Disorder: Practice Guidelines from a Critical Interpretive Synthesis (CIS) Systematic Review

Abstract: Parent carers of children with Autism Spectrum Disorder (ASD) often report increased levels of stress, depression, and anxiety. Unmet parent carer mental health needs pose a significant risk to the psychological, physical, and social well-being of the parents of the child affected by ASD and jeopardize the adaptive functioning of the family as well as the potential of the child affected by ASD. This systematic review identifies key qualities of interventions supporting the mental health of parent carers and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
91
0
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(104 citation statements)
references
References 101 publications
5
91
0
8
Order By: Relevance
“…Moreover, this study is consistent with the meta-analyses (Catalano et al, 2018;Da Paz & Wallander, 2017) that have demonstrated the role and effectiveness of group CBT and stress management dealing with parents' perspectives and emerging problem-solving skills to improve maternal mental health.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, this study is consistent with the meta-analyses (Catalano et al, 2018;Da Paz & Wallander, 2017) that have demonstrated the role and effectiveness of group CBT and stress management dealing with parents' perspectives and emerging problem-solving skills to improve maternal mental health.…”
Section: Discussionsupporting
confidence: 89%
“…The most promising interventions included cognitive behavioral therapy (CBT), stress management skills, relaxation techniques, expressive writing, mindfulness-based stress reduction, and acceptance and commitment therapy. And in a systematic review by Catalano et al (2018) evaluated 23 studies conducted in 13 countries, including Jordan, on the use of therapeutic programs to improve the mental health of parents of children with AD, with the specific aim of identifying the basic features common to all these interventions. They reported that therapeutic interventions should encompass parental self-perspective-taking and real-time problem-solving.…”
mentioning
confidence: 99%
“…, Catalano et al . ) and that more directed parent support is needed (Siklos and Kerns ; Smith et al . ; Cadman et al .…”
mentioning
confidence: 99%
“…Similar to other research, levels of parental stress were elevated compared to population expectations for the United Kingdom. The mental well-being of parents of children with ASD has been highlighted as an important area of research [Catalano, Holloway, & Mpofu, 2018] and numerous interventions have been evaluated [Da Paz & Wallander, 2017]. The data from the current trial suggest that, in future studies, parental well-being outcomes should be assessed among the outcomes and/or examined as moderators of intervention effectiveness.…”
Section: Discussionmentioning
confidence: 94%